The provincials : a personal history of Jews in the South / Eli N. Evans ; with photographs and a new introduction by the author ; foreword by Willie Morris. - Evans, Eli N. (North Carolina history & culture anthology., 2005)
This portrait of Jews in the South takes readers inside the nexus of southern and Jewish histories, from the earliest immigrants to the present day. This edition includes a gallery of more than two dozen family and historical photographs as well as a new introduction by the author.